Metodologias artísticas de pesquisa em educação e deslocamento na formação docente: a fotografia como construção do pensamento visual - Egas, Olga Maria Botelho (2017)
What can we teach / learn about education with photography? This was the starting point for investigating how photographic images make visible problems related to teaching and learning. From the experience as a trainer of future teachers in the Pedagogy and graduation in Visual Arts course at the Federal University of Juiz de Fora, Minas Gerais and in the Masters in Visual Arts and Education: a constructivist approach of the University of Granada, Spain, are explored Aspects of teaching through images. In this field, The photographs produced by the author during the period from 2013 to 2016 - main study material - point to thoughts, worries and restlessness that occurred during the lessons and in the field research. Thus, the present study is based mainly on the Artistic Methodologies of Research in Education, proposed by Ricardo Marin Viadel and Joaquín Roldán (2012), which has in the photograph its essence and object, its theoretical field and methodological procedure. The visual knowledge produced in this research made it possible to reflect on new ways of contemplating educational phenomena and to extend the interdisciplinary boundaries between Art, Cultures and Education. Above all, the research focused on interactions between teaching and research with the knowledge inherent in the place of the teacher-artist in teacher training.